The genetics of pre-eclampsia and other hypertensive disorders of pregnancy - Williams, Paula J.; Broughton Pipkin, Fiona (Elsevier, 2011)
Hypertension is the most frequent medical complication occurring during pregnancy. In this chapter, we aim to address the genetic contribution to these disorders, with specific focus on preeclampsia. The pathogenic mechanisms underlying pre-eclampsia remain to be elucidated; however, immune maladaptation, inadequate placental development and trophoblast invasion, placental ischaemia, oxidative stress and thrombosis are all thought to represent key factors in the development of disease. Furthermore, all of these components have genetic factors that may be involved in the pathogenic changes occurring. The familial nature of pre-eclampsia has been known for many years and, as such, extensive genetic research has been carried out in this area using strategies that include candidate gene studies and linkage analysis. Interactions between fetal and maternal genotypes, the effect of environmental factors, and epistasis will also be considered.